(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The study investigated radio drama as a synergy for social change. The research design for this study will be a qualitative type of research. The population of the study consisted of all government workers in Ekiti State. The sample size of one hundred fifty (150) respondents was used for the study. The instrument that was used is a self-structured questionnaire for data collection. The data gathered for this study will be analysed using percentage distribution of frequency counts and bar chart to analyse the demographic data of the respondent. It was concluded that radio drama can be very effective in political campaign and political propaganda. Radio drama has positive influence on behavioural change in the society. Since majority of the radio drama programme is focusing mainly on issues affecting the society, hence radio drama influences behavioural change in the society. Radio drama has more effectiveness to social change than other form of drama. It was recommended that drama should be use to educate listeners on important social issues, such as education and civil rights, radio drama has high potency in effective communication hence, it should be adopted where other means of communication fail.